Implementasi Model Pembelajaran STAD Untuk meningkatkan Aktifitas Siswa Pada Pembelajaran Ekonomi Kelas XI SMA - Ajun Ajun (Universitas Mathla'ul Anwar Banten, 2019)
Learning the Students Teams Achievement Division (STAD) model is one of cooperative learning in which students learn in small groups with a diversity of levels of research learning abilities aimed to improve learning outcomes and student activities in the process of economic learning in the management concept. This study uses a Classroom Action Research (action research) which consists of 3 cycles. The results of the study show that the STAD learning model can improve student learning outcomes and activities for students who have high academic abilities or students who have low academic ability in the subject matter of management economics